Personal air vehicle (PAVE) application in Malaysia - Romli, Fairuz Izzudin; Yaakob, Mohd Saffuan (IEEE, 2014)
Transportation has become a huge necessity in our life today, which is instrumental to create greater socioeconomic opportunities. As the world progresses, transportation systems will undergo paradigm shifts to suit with changing requirements. Personal transportation is often preferred to the public transport and to date, most of them have been made on the ground through roads. However, with the increasing traffic volume, the average time spent travelling on roads has significantly increased for the same amount of distance travelled. It has already been proposed that utilization of the possible third dimension of transportation system, which is the air transport, can facilitate in supporting the personal transportation and subsequently alleviate this problem. This notion gives birth to the design concepts of the personal air vehicle (PAVE) that is envisioned to operate synergistically with ground and air infrastructures. This paper aims to preliminarily study and analyze the potential benefits of having PAVE option in Malaysia for domestic travel and how its performance will fare in comparison to the existing ground transportation options. The results of travel time and cost comparisons highlight the potential of PAVE application for the domestic transportation in Malaysia, particularly for personal travel need.